Does Aggregated Returns Disclosure Increase Portfolio Risk Taking? - Beshears, John; Choi, James J.; Laibson, David; Madrian, Brigitte C. (Review of Financial Studies, 2017)
Many experiments have found that participants take more investment risk if they see returns less frequently, see portfolio-level returns (rather than each individual asset's returns), or see long-horizon (rather than one-year) historical return distributions. In contrast, we find that such information aggregation treatments do not affect total equity investment when we make the investment environment more realistic than in prior experiments. Previously documented aggregation effects are not robust to changes in the risky asset's return distribution or the introduction of a multi-day delay between portfolio choice and return realizations.